ANALYSIS OF THE LINGUOCULTURAL MEANINGS OF THE NAMES OF THE PEOPLE IN KARAKALPAK, DASTANS - Karjawbaev Orazali Esbosin uli; Toleubayeva A.O (Лучшие интеллектуальные исследования, 2024)
Abstract: The study of common names' linguistic and cultural connotations in Karakalpak folklore is the focus of this essay. According to the author, they are messengers of knowledge about the people's psyche, history, culture, and way of life. The current state of the language and the impact of extensive onomastic research into its folk art on its evolution are the main topics of discussion in this article. In particular, the human names used in Karakalpak folklore are discussed, as they had a significant influence on the long-standing customs of name-giving among the Karakalpak people.